2019
DOI: 10.1080/14740338.2020.1694659
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of empagliflozin in Japanese patients with type 2 diabetes: interim analysis from a post-marketing surveillance study

Abstract: Background: Sodium-glucose cotransporter-2 (SGLT2) inhibitors are effective treatments for type 2 diabetes mellitus (T2DM). We present the interim findings of an ongoing post-marketing surveillance (PMS) study in Japanese patients with T2DM receiving empagliflozin. Research design and methods: This 3-year, prospective, observational, multicenter PMS evaluated the safety and effectiveness of empagliflozin in Japanese clinical practice. Patients with T2DM who had not been treated with empagliflozin before enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…In this study, 38.8% of polyuria/pollakiuria events occurred within 7 days after administration, and most events (89.4%) recovered or were in remission. A relatively high incidence of polyuria/ pollakiuria has also been reported in the interim reports of post-marketing surveillance studies of the other SGLT2 inhibitors in Japanese T2DM patients [32,33,34,35]. This ADR may be expected based on the mechanism of action of SGLT2 inhibitors, which have been shown to increase urine volume [36], although the actual change in urine volume was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, 38.8% of polyuria/pollakiuria events occurred within 7 days after administration, and most events (89.4%) recovered or were in remission. A relatively high incidence of polyuria/ pollakiuria has also been reported in the interim reports of post-marketing surveillance studies of the other SGLT2 inhibitors in Japanese T2DM patients [32,33,34,35]. This ADR may be expected based on the mechanism of action of SGLT2 inhibitors, which have been shown to increase urine volume [36], although the actual change in urine volume was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Collectively, these results should provide assurance to patients and physicians about the overall safety of tofogliflozin during long‐term use. Based on indirect comparisons, the incidence of overall ADRs (12.61%) observed in this surveillance is equivalent to that of the other post‐marketing studies of SGLT2 inhibitors (ipragliflozin, 10.71% over a period of 2 years 33 ; canagliflozin, 9.09% over a period of 1 year 34 ; empagliflozin, 8.5% over a period of 3 years 35 ).…”
Section: Discussionmentioning
confidence: 64%
“…Regarding the safety of canagliflozin, the types of ADRs reported in this surveillance were also recorded in the clinical trial program [ 2 ] and were generally similar to those reported for other SGLT2 inhibitors [ 18 – 21 ]. Most of the ADRs with an incidence of ≥ 0.1% have already been listed in the package insert for canagliflozin [ 1 ].…”
Section: Discussionmentioning
confidence: 61%